Klippel-Trenaunay-Weber syndrome: a case with cerebral and cerebellar hemihypertrophy and a review of the literature - Anlar, Banu; Yalaz, Kalbiye; Erzen, Canan (The Turkish Journal of Pediatrics, 1988)
A case with Klippel-Trenaunay-Weber syndrome and macrocephaly in whom left cerebral and cerebellar hemihypertrophy were demonstrated by computerized cranial tomography is reported. The relevant literature is reviewed and the complications and the therapeutic methods of the syndrome are summarized.
Keywords: angiomatosis; Klippel-Trenaunay-Weber syndrome; computerized tomography